The Production and Decomposition Rate of Mangrove Litter in The Sungai Alam Village, Bengkalis Sub-district, Bengkalis Regency, Riau Province - Novita Sari Br Perangin-angin; Adriman '; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research has been done on february 2014 in Sungai Alam Village, Bengkalis Subdistrict,Bengkalis Regency, Riau Province. A research aims to understand the Productionand Decomposition Rate of Mangrove Litter in Sungai Alam Village. There were 3 stationsand 3 plots in each station (station 1 in the mangrove conservation, station 2 in the goodmangrove forest and station 3 in the mangrove exploited wisely). In each plot, 1 net 1 x 1 m2were placed mangrove dominant. This net 2 meters above the mangrove forest floor. The bag(nets 20 cm x 10 cm) was filled with 10 grams litter and used for studying the litterdecomposition rate. The bag were placed in forest floor still be suffused of water. Sampel forlitter production, decomposition rate and water quality were taken once of 7 days (3 times).Results shown the highest litter production was ini St 2 (52,5 gr/m2/day) and thelowest was in the St 1 (25,151 gr/m2/day). Decomposition rate of the litter in each samplingpoints was relatively low in the 1st week and become faster in the 3st week. The highestdecomposition rate litter mangrove (lief, stick, flower or fruit) was in the St III, while thelowest was in the St 1.Keywords : Mangrove litter, litter decimposition rate, Sungai Alam, Riau